2017
DOI: 10.1177/1010428317702899
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA signature associated with pathological complete response to novel neoadjuvant therapy regimen in triple-negative breast cancer

Abstract: Neoadjuvant chemotherapy aims to improve the outcome of breast cancer patients, but only few would benefit from this treatment. Pathological complete response has been proposed as a surrogate marker for the prediction of long-term clinical benefits; however, 50%-85% patients have an unfavorable pathological complete response to chemotherapy. MicroRNAs are known biomarkers of breast cancer progression; nevertheless, their potential to identify patients with pathological complete response remains poorly understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Previous studies reported on the roles of the expression of certain miRNAs, such as miRNA-18a, miRNA-7 and miRNA-340, in the tumor tissue of patients who achieved PCR in predicting survival outcomes and response to chemotherapy. [24][25][26][27] The association between miRNA-21 expression and clinicopathological features in our study demonstrated an upregulation of this biomarker for clinical stages II and III, axillary lymph node metastasis and all breast cancer subtypes regardless of previous treatment with NAC. Conversely, there were no significant correlations of miRNA-21 expression with tumor size or tumor histological grade, which is in accordance with the findings of previous reports.…”
Section: Discussionsupporting
confidence: 54%
“…Previous studies reported on the roles of the expression of certain miRNAs, such as miRNA-18a, miRNA-7 and miRNA-340, in the tumor tissue of patients who achieved PCR in predicting survival outcomes and response to chemotherapy. [24][25][26][27] The association between miRNA-21 expression and clinicopathological features in our study demonstrated an upregulation of this biomarker for clinical stages II and III, axillary lymph node metastasis and all breast cancer subtypes regardless of previous treatment with NAC. Conversely, there were no significant correlations of miRNA-21 expression with tumor size or tumor histological grade, which is in accordance with the findings of previous reports.…”
Section: Discussionsupporting
confidence: 54%
“…As for miR-9-3p, although less intensively investigated in breast cancer, it has been identified as a tumor suppressor in claudin-low breast cancer cells 44 . Moreover, downregulation of miR-9-3p was reported to be related to worse clinical chemotherapy response in breast cancer 45 . However, the specific role of miR-9-3p in TNBC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…One of the identified miRNAs, miR-134-5p, was reported in rats to exhibit a significantly down-regulated expression after seven days of lactation compared with the expression level on the first day of lactation [33]. Another miRNA, miR-143-5p, is down-regulated in breast cancer [34]. Thus, miR-134-5p and miR-143-5p have the potential to be bound by circHIPK3 and have functions related to breast function and lactation, so these should be further investigated as targets of circHIPK3 that potentially explain its role in breast development or diseases.…”
Section: Discussionmentioning
confidence: 99%